INNOVATIVE SUNFLOWER PLOT TRIAL HEADER FOR A PLOT COMBINE - V. D. Shaforostov; S. S. Makarov; P. A. Elizarov (Сельскохозяйственные машины и технологии, 2016)
One of the parameters affects the quality of sunflower harvesting is a combination of varietal characters. If the harvesting equipment do not meet to these trappings it would lead to a yield losses. The aim of this research is a plot combine sunflower header improving to provide stretching of sunflower stem regardless of plant length and harvesting sunflower varieties with branched inflorescence for preventing heads and seeds losses. Different types of plot combine header feeding devices were analyzed. As the result auger (screw type) feeder defined as a more reliable and simplest. The 2-row header prototype was constructed. Main adjustable parameters are collated to a botanical features of a harvesting plants. The stem cutting length is 5-10 cm for an ordinary sunflower varieties and 15-25 cm for a branched varieties. The new header losses do not exceed 0.15 percent for single seeds and 3.3 persent for heads in case of branched sunflower harvesting.